Oxide-based solid electrolyte material and preparation method and application thereof
The raw materials and additives of the oxide-based solid electrolyte are uniformly mixed and calcined through the dry mixing method, which solves the problems of material expansion and wall sticking in the wet preparation, realizes the efficient preparation of the oxide-based solid electrolyte, and improves the efficiency of the oxide-based solid electrolyte. Its physical phase purity and battery safety performance.
Patent Information
- Application Number
- CN202411369041.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-24
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-29
AI Technical Summary
In the existing preparation methods of oxide-based solid electrolytes, wet mixed raw materials have severe expansion and overflow and material sticking problems during high-temperature calcination, resulting in low production efficiency and low material utilization.
Using the dry mixing method, the raw materials of the oxide-based solid electrolyte and the additives I (such as magnesium oxide, silicon oxide, silicate compounds) and additives II (such as polymer materials) are evenly mixed to form a precursor. Then, a calcination treatment is performed to prepare an oxide-based solid electrolyte.
Through the dry mixing method, the hydrophobicity and fluidity of the material surface are improved, the volume expansion and wall sticking phenomenon of the material are reduced, high phase purity and high fluidity are maintained, and the safety performance of the battery is improved.
Smart Images

Figure CN119330700A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of methods or devices for directly converting chemical energy into electrical energy, and in particular to an oxide-based solid electrolyte material and a preparation method and application thereof. Background Art
[0002] Inorganic solid electrolytes are a class of ceramic materials with high ion conductivity for lithium (Li), sodium (Na) or other alkali metal ions, which can provide a stable and efficient transmission medium for the ion flow between the positive and negative electrodes in the battery. According to the different chemical properties of the anions, inorganic solid electrolytes are mainly divided into oxide-based solid electrolytes, sulfide-based solid electrolytes and halide-based solid electrolytes. Among them, oxide-based solid electrolytes can be divided into NASICON type, garnet and perovskite type according to their structural characteristics. These materials can be used as an effective substitute for organic liquid electrolytes in high energy density lithium batteries or sodium batteries due to their inherent non-flammability, wider electrochemical stability window and better thermal stability.
[0003] At present, the preparation method of oxide-based solid electrolyte includes solid phase method, sol-gel method, coprecipitation method, etc., and these preparation methods mostly use wet mixed raw materials; however, in the actual application process, it is found that the raw materials mixed by wet method have serious expansion overflow and material sticking wall problems during high temperature calcination, resulting in low production efficiency and low material utilization. In view of this problem, a method for preparing solid electrolyte by dry method is disclosed in the prior art (CN114824452A), by adding organic additives to the raw materials for preparation, and combining with dry mixing and stirring mixed raw materials, using organic additives to improve the fluidity and moisture retention of materials, so as to avoid the material from sticking to the crucible wall during calcination, and using high moisture retention to effectively alleviate the problem of gas discharge causing material expansion; although the method can reduce the volume expansion of materials during sintering to a certain extent and reduce its sticking wall, the degree of improvement is limited. In addition, the oxide-based solid electrolytes obtained by the existing preparation method are mostly irregularly shaped particles, resulting in a low tap density of the corresponding material. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide an oxide-based solid electrolyte and a preparation method and application thereof.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] In a first aspect, the present invention provides a method for preparing an oxide-based solid electrolyte, wherein the raw materials and additives of the oxide-based solid electrolyte are mixed evenly by dry mixing to obtain a precursor; and then the precursor is calcined to obtain the oxide-based solid electrolyte;
[0007] The auxiliary agent includes auxiliary agent I and auxiliary agent II, the auxiliary agent I includes at least one of magnesium oxide, silicon oxide and silicate compounds, and the auxiliary agent II is a polymer material.
[0008] The present invention combines specific additives I and II, which can not only improve the hydrophobicity of the material surface to reduce the water carried, and improve the fluidity of the material during the sintering process to reduce the material sticking to the wall, but also effectively absorb the water vapor generated during the calcination process to inhibit the gas production rate to reduce the volume expansion of the material; at the same time, it can also make the prepared oxide-based solid electrolyte maintain a high phase purity, and give the oxide-based solid electrolyte high fluidity, so as to improve its tap density when used as a component of the composite positive electrode material, thereby improving the safety performance of the battery.
[0009] Optionally, the silicate compound may specifically be at least one of methyl silicate, ethyl silicate and tetraethyl silicate.
[0010] As a preferred embodiment of the method for preparing the oxide-based solid electrolyte of the present invention, the mass fraction of the additive I relative to the total mass of the raw materials of the oxide-based solid electrolyte is 0.1% to 10%. Optionally, the mass fraction of the additive I relative to the total mass of the raw materials of the oxide-based solid electrolyte can be 0.5%, 0.9%, 1.2%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%.
[0011] The study found that the amount of additive I added affects the fluidity of the material during calcination and the phase purity of the oxide solid electrolyte; the additive I in the above-mentioned addition range can maintain the high phase purity of the oxide solid electrolyte while being more evenly distributed on the surface of the raw material particles, enhancing the fluidity of the material during calcination to more effectively reduce the material sticking to the wall, and at the same time better inhibiting the volume expansion. In addition, the additive I can be mixed with one or several raw materials of the oxide-based solid electrolyte first, and then mixed with other remaining raw materials; the additive I can also be directly mixed with all the raw materials of the oxide-based solid electrolyte.
[0012] As a preferred embodiment of the method for preparing the oxide-based solid electrolyte of the present invention, the mass fraction of the auxiliary agent II relative to the total mass of the raw materials of the oxide-based solid electrolyte is 0.1% to 5%. Alternatively, the mass fraction of the auxiliary agent II relative to the total mass of the raw materials of the oxide-based solid electrolyte can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%.
[0013] The study found that the amount of additive II added will affect the volume expansion rate of the material during calcination and the physical purity of the oxide solid electrolyte; the additive II in the above-mentioned addition range can maintain the high physical purity of the oxide solid electrolyte while fully absorbing water vapor and slowing down gas production during the calcination process to better inhibit the expansion of the material.
[0014] As a preferred embodiment of the method for preparing the oxide-based solid electrolyte of the present invention, the polymer material includes at least one of polyethylene glycol, polyethylene oxide, polyvinyl alcohol, polyvinyl butyral, methyl cellulose, ethyl cellulose, carboxymethyl cellulose, microcrystalline cellulose, and glucose.
[0015] As a preferred embodiment of the method for preparing the oxide-based solid electrolyte of the present invention, the precursor is a spherical particle or a quasi-spherical particle. Studies have found that when the precursor is a spherical particle or a quasi-spherical particle, the spherical morphology can provide more exhaust gaps during the sintering of the material so that the generated gas can be fully discharged, which is more conducive to reducing volume expansion; in addition, the spherical morphology can further reduce the mutual adhesion between materials and the adhesion of materials to the wall.
[0016] Optionally, the spherical or quasi-spherical precursor particles can be prepared by a drum granulator, wherein the rotation speed of the drum granulator is 3-7 rpm, the slope is 3%-4%, and the granulation time is 24-26 h; preferably, the rotation speed of the drum granulator is 5 rpm, the slope is 3.5%, and the granulation time is 26 h.
[0017] As a preferred embodiment of the method for preparing the oxide-based solid electrolyte of the present invention, the particle size D of the spherical particles or quasi-spherical particles is 50 Optionally, the particle size D of the spherical particles or quasi-spherical particles is 50 Specifically, it can be 1μm, 3μm, 5μm, 7μm, 9μm, 11μm, 13μm, 15μm, 17μm, and 19μm.
[0018] As a preferred embodiment of the method for preparing the oxide-based solid electrolyte of the present invention, the calcination treatment comprises: calcining at 700-1500° C. for 5-20 h (i.e., the calcination treatment is performed only once);
[0019] Alternatively, first calcine at 200-800°C (primary calcination) for 2-15h, take out and grind, then continue calcining at 600-1500°C (secondary calcination) for 5-20h (i.e., the calcination treatment is performed twice).
[0020] At the same time, nitrogen, oxygen, argon or dry compressed air can be introduced during the calcination process to quickly remove the waste gas, water vapor, etc. generated during the sintering process, further slowing down the expansion of the material and reducing the material sticking to the wall.
[0021] Optionally, the main function of the primary calcination is to discharge waste gas and water vapor, and the temperature can be 300°C, 400°C, 500°C, 600°C, or 700°C, and the time can be 4h, 6h, 8h, 10h, 12h, or 14h; the main function of the secondary calcination is to sinter the powder into a solid solution, and the temperature can be 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, or 1400°C, and the time can be 6h, 8h, 10h, 12h, 14h, 16h, or 18h.
[0022] As a preferred embodiment of the preparation method of the oxide-based solid electrolyte of the present invention, the oxide-based solid electrolyte is one of garnet-type solid electrolyte materials, NASCION-type solid electrolyte materials, LISCION-type solid electrolyte materials, perovskite-type solid electrolyte materials and their derivative materials. Optionally, the oxide-based solid electrolyte can be Li 1+x Al x Ti 2-X P 3 O 12 , Li 6+x La 3 Zr 2-x Ta x O 12 , Li 0.33 La 0.56 TiO 3 , Li 14 Zn(GeO 4 ) 4 , Li 2 PO 2 N et al.
[0023] In a second aspect, the present invention provides an oxide-based solid electrolyte prepared by the above preparation method.
[0024] In a third aspect, the present invention provides the use of the above oxide-based solid electrolyte in batteries or capacitors.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention combines specific additives I and II, which can not only improve the hydrophobicity of the material surface to reduce the water carried, and improve the fluidity of the material during the sintering process to reduce the material sticking to the wall, but also effectively absorb the water vapor generated during the calcination process to inhibit the gas production rate to reduce the volume expansion of the material; at the same time, it can also make the prepared oxide-based solid electrolyte maintain a high phase purity, and give the oxide-based solid electrolyte high fluidity, so as to improve its tap density when used as a component of the composite positive electrode material, thereby improving the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the oxide-based solid electrolyte prepared in Example 1 (magnified 10,000 times);
[0028] Figure 2 This is a SEM image of the oxide-based solid electrolyte prepared in Example 1 (magnified 20,000 times);
[0029] Figure 3 This is a physical photo of the oxide solid electrolyte prepared in Example 1 (not broken);
[0030] Figure 4 This is a physical photograph of the oxide solid electrolyte prepared in Comparative Example 3 (not broken). DETAILED DESCRIPTION
[0031] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0032] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.
[0033] Examples 1 to 8 and Comparative Examples 1 to 4
[0034] The method for preparing the oxide-based solid electrolyte of the present invention comprises the following steps:
[0035] S1. Based on the total mass of the raw materials of the oxide-based solid electrolyte being 100%, 9.7wt% of lithium carbonate, 3.7wt% of aluminum oxide, 23.4wt% of titanium oxide and 63.2wt% of diammonium phosphate were added together with the additives into a VC mixing device and mixed for 40 minutes;
[0036] S2. The uniformly mixed materials in S1 are added into a turbine for high-speed rotation to form a precursor, and then the precursor is calcined at 400°C for 10 hours and then further calcined at 800°C for 12 hours to obtain an oxide-based solid electrolyte.
[0037] Table 1 Additives in Examples 1 to 8 and Comparative Examples 1 to 4 and their addition amounts relative to the total mass of each raw material of the oxide-based solid electrolyte
[0038]
[0039] The addition amounts of additive I and additive II in Table 1 refer to the mass fraction of additive I or additive II relative to the total mass of the raw materials of the oxide-based solid electrolyte.
[0040] Example 9
[0041] An embodiment of the preparation method of the oxide-based solid electrolyte of the present invention is basically the same as that of Example 1, except that the raw materials and their mass fractions of the oxide-based solid electrolyte in step S1 are: 6.6wt% Li 2 CO 3 , 50.0wt% La 2 O 3 and 43.4wt% TiO 2 ; Additive I is tetraethyl silicate, and its addition amount relative to the total mass of all raw materials of the oxide-based solid electrolyte is 2wt%; Additive II is polyvinyl butyral, and its addition amount relative to the total mass of all raw materials of the oxide-based solid electrolyte is 0.5wt%.
[0042] Performance Testing
[0043] 1. Phase purity: The oxide-based solid electrolytes prepared in each embodiment and comparative example were subjected to XRD test to obtain the XRD diffraction pattern of the oxide-based solid electrolyte, and then the intensities of the diffraction peaks of the main phase and the impurity phase in the XRD diffraction pattern were analyzed and counted, and the phase purity was calculated by the following formula;
[0044] Phase purity (%) = main phase diffraction peak intensity / (main phase diffraction peak intensity+extra phase diffraction peak intensity)×100%.
[0045] 2. Expansion rate: Under the conditions of temperature of 25° C. and air pressure of 101 KPa, the volume of the precursor before sintering and the volume of the oxide-based solid electrolyte after sintering in each embodiment and comparative example were tested, and the volume expansion rate was calculated using the following formula, wherein the height of the sagger input for each batch during production was about 40 mm;
[0046] Expansion rate (T) = (V 2 -V 1 ) / V 1 ×100%; where V 1 is the volume of the precursor, in cm 3 ; V 2 is the volume of the oxide-based solid electrolyte in cm 3.
[0047] 3. Angle of repose: Measured according to the standard "GB 6521-1986 Determination of angle of repose of alumina powder".
[0048] Table 2 Properties of oxide-based solid electrolytes in various embodiments and comparative examples
[0049] serial number Phase purity / % Expansion rate / % Is it sticky to the wall? Angle of repose / ° Example 1 98% -22.5% no 30 Example 2 94% 3.7% no 32 Example 3 92% -19.6% no 33 Example 4 85% -17.8% no 35 Example 5 96% -20.5% no 32 Example 6 95% -15.3% no 33 Example 7 98% -14.6% no 32 Example 8 96% -13.7% no 31 Example 9 96% -18.0% no 31 Comparative Example 1 95% 12% yes 55 Comparative Example 2 96% 47% no 36 Comparative Example 3 81% 33% no 38 Comparative Example 4 67% 53% no 36
[0050] According to the data in Table 2, the phase purity of the oxide-based solid electrolyte in Examples 1 to 9 reaches more than 85%, the expansion rate is less than or equal to 3.7%, and no wall adhesion occurs during the calcination process, and the repose angle is less than or equal to 35°, indicating that the preparation method of the oxide-based solid electrolyte of the present invention can effectively improve the wall adhesion of the material during the sintering process, and reduce the volume expansion of the material, while making the obtained oxide-based solid electrolyte have high phase purity and high fluidity. In addition, according to Comparative Examples 1 and 2, it can be seen that it is difficult to simultaneously improve the wall adhesion and volume expansion problems of the material during the sintering process by using auxiliary agent I (magnesium oxide) or auxiliary agent II (polyethylene oxide); and it can be found from Comparative Examples 3 and 4 that when calcium stearate or calcium oxide is used as auxiliary agent I and auxiliary agent II (polyethylene oxide), it is not only difficult to effectively reduce the volume expansion of the material, but also the phase purity of the obtained oxide-based solid electrolyte is reduced.
[0051] In addition, according to Figure 3 It can be seen that compared with the volume of the precursor before sintering, the volume of the oxide-based solid electrolyte after sintering in Example 1 did not expand, but shrunk; Figure 4 It can be found that compared with the volume of the precursor before sintering, the volume of the oxide-based solid electrolyte after sintering in Comparative Example 3 has expanded significantly, further proving that the preparation method of the oxide-based solid electrolyte of the present invention can effectively reduce the volume expansion of the material during the sintering process.
[0052] 4. SEM test: The oxide-based solid electrolytes prepared in each embodiment were subjected to SEM (scanning electron microscope) test, wherein the SEM image of the oxide-based solid electrolyte in Example 1 is as follows: Figure 1 and Figure 2 As shown, according to Figure 1 and Figure 2 It can be seen that the secondary particles of the oxide-based solid electrolyte are spherical or quasi-spherical, and the secondary particles of the oxide-based solid electrolyte in Examples 2 to 9 are basically the same as those in Example 1, which are all spherical or quasi-spherical. The oxide-based solid electrolyte particles of this morphology can be more densely stacked due to their regular geometric shape, thereby improving the volume energy density of the battery. Moreover, the spherical or quasi-spherical particles have better fluidity during mixing and coating, which helps to improve the efficiency and consistency of battery production.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an oxide-based solid electrolyte, characterized in that: The raw materials and additives of the oxide-based solid electrolyte are mixed evenly by dry mixing to obtain a precursor; the precursor is then calcined to obtain the oxide-based solid electrolyte; The auxiliary agent includes auxiliary agent I and auxiliary agent II, the auxiliary agent I includes at least one of magnesium oxide, silicon oxide and silicate compounds, and the auxiliary agent II is a polymer material.
2. The preparation method according to claim 1, characterized in that The mass fraction of the auxiliary agent I relative to the total mass of the raw materials of the oxide-based solid electrolyte is 0.1% to 10%.
3. The preparation method according to claim 1, characterized in that: The mass fraction of the auxiliary agent II relative to the total mass of the raw materials of the oxide-based solid electrolyte is 0.1% to 5%.
4. The preparation method according to claim 1, characterized in that: The polymer material includes at least one of polyethylene glycol, polyethylene oxide, polyvinyl alcohol, polyvinyl butyral, methyl cellulose, ethyl cellulose, carboxymethyl cellulose, microcrystalline cellulose and glucose.
5. The preparation method according to claim 1, characterized in that: The precursor is spherical particles or quasi-spherical particles.
6. The preparation method according to claim 5, characterized in that: The particle size D of the spherical particles or quasi-spherical particles 50 0.5~20μm.
7. The preparation method according to claim 1, characterized in that: The calcination treatment comprises: calcining at 700-1500° C. for 5-20 hours; Alternatively, first calcine at 200-800°C for 2-15h, take out and grind, then continue calcining at 600-1500°C for 5-20h.
8. The preparation method according to claim 1, characterized in that: The oxide-based solid electrolyte is one of garnet-type solid electrolyte materials, NASCION-type solid electrolyte materials, LISCION-type solid electrolyte materials, perovskite-type solid electrolyte materials and derivative materials thereof.
9. An oxide-based solid electrolyte obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the oxide-based solid electrolyte according to claim 9 in batteries or capacitors.
Citation Information
Patent Citations
Preparation method of fluorescent transparent ceramic disk for LED (Light-emitting Diode)
CN105503188A
Method for preparing solid electrolyte by dry method and application thereof
CN114824452A
Solid electrolyte material and preparation method thereof, battery and electric equipment
CN117691174A
Solid electrolyte and preparation method and application thereof
CN118561256A
Battery Disconnect Apparatus
KR102765639B1
Cited By
Si-O-M-based solid electrolyte and preparation method and battery application thereof
CN120923246A